Feeder Pig Nursery Cost Return Projection - Dhuyvetter, Kevin C.; Tokach, Mike D.; Dritz, Steve S. (My University, 2007)
This publication provides estimated cost and returns for a feeder pig nursery.
MF2151_2007_10
Keywords: MF2151; Livestock; Economics; MF